2023
DOI: 10.1186/s12974-023-02757-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of 25 cerebrospinal fluid cytokines in a case–control study of 106 patients with recent-onset depression and 106 individually matched healthy subjects

Abstract: Background Neuroinflammation has been suggested as a contributor to the pathophysiology of depression; however, large case–control studies investigating cytokine levels in the cerebrospinal fluid (CSF) from patients with recent-onset depression by multiplex analyses are missing. Methods An individually matched (sex and age) prospective case–control study comparing patients with recent-onset depression to healthy controls. CSF was analyzed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Our research sheds light on the role of less-studied chemokines in depression. Elevated CCL2 in blood, CSF, and in post-mortem brain tissues of depressed patients (Young, Bruno, and Pomara 2014; Eyre et al 2016; Sørensen et al 2023; Torres-Platas et al 2014), alongside mixed data for CCL4 (Camacho-Arroyo et al 2021; Sørensen et al 2023; Leighton et al 2018) and limited research on CCL13, with only one study that found lower levels in suicide attempters (Janelidze et al 2013), indicate their intricate roles in this symptom spectrum. Additionally, it highlighted PlGF, part of the vascular endothelial growth factor family (De Falco 2012), implicated in angiogenesis, the immune response, and obesity-related processes (Oura et al 2003; Lijnen et al 2006), which was previously found to have lower levels in depressed patients (Yue et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research sheds light on the role of less-studied chemokines in depression. Elevated CCL2 in blood, CSF, and in post-mortem brain tissues of depressed patients (Young, Bruno, and Pomara 2014; Eyre et al 2016; Sørensen et al 2023; Torres-Platas et al 2014), alongside mixed data for CCL4 (Camacho-Arroyo et al 2021; Sørensen et al 2023; Leighton et al 2018) and limited research on CCL13, with only one study that found lower levels in suicide attempters (Janelidze et al 2013), indicate their intricate roles in this symptom spectrum. Additionally, it highlighted PlGF, part of the vascular endothelial growth factor family (De Falco 2012), implicated in angiogenesis, the immune response, and obesity-related processes (Oura et al 2003; Lijnen et al 2006), which was previously found to have lower levels in depressed patients (Yue et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have employed case-control designs to find differences in immune markers between individuals with depression and healthy controls (Wittenberg et al 2020; Sørensen et al 2023; Sforzini et al 2023). At the same time, various studies have established the link between specific depressive symptom profiles and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have measured five, 16 six, 14 or 27 (the lower limit of detection was often limited) 18 proteins in multiplex immunoassays. However, only two (IL‐8 and MCP‐1) of 13 cytokines were detected in CSF samples from the first episode of schizophrenia in a multiplex immunoassay.…”
Section: Discussionmentioning
confidence: 99%
“… 17 CSF IL‐4 (significant even after correction for multiple comparisons), macrophage inflammatory protein (MIP)‐1β, and MCP‐1 were all higher in 106 patients with recent‐onset depression compared to 106 healthy controls, while no association was observed between cytokines and severity of depressive or depression comorbid‐anxiety symptom scores. 18 …”
Section: Multiplex Immunoassay Findingsmentioning
confidence: 99%
See 1 more Smart Citation